L’autocrazia e la crisi - Prospero, Michele (Bollettino Filosofico, 2025)
Marx lived through five major crises and addressed them in his economic manuscripts, historical writings, and notebooks of extracts, many of which have only recently been published in the Marx-Engels-Gesamtausgabe. This article examines Karl Marx's theoretical and empirical analysis of the interaction between economic crises (the cyclical nature of capitalist economies, the recurrence of crises) and authoritarian regimes (the illiberalism of political government, particularly in France under the Bonapartist regime). In contrast to a deterministic approach, Marx observed how state intervention – through monetary policies, unproductive government spending, and credit manipulation – could temporarily mitigate economic crises, stabilize markets, social security, and prolong the duration of Bonapartism as both a repressive and modernizing force, capable of managing cyclical crises while aggravating social contradictions. Keywords: Autocracy, Crisis of Legitimization, Economic Crisis, Political Capitalism, State Intervention